New Zr-Ti-Nb Alloy for Medical Application: Development, Chemical and Mechanical Properties, and Biocompatibility - Mishchenko, O.; Ovchynnykov, O.; Kapustian, O.; Pogorielov, M.; Міщенко, Олег Миколайович; Овчинник, О.; Капустян, О.; Погор’єлов, М. (My University, 2020)
The concept of mechanical biocompatibilities is considered an important factor for orthopedics and dental implants. The high Young modulus of traditional Ti-based alloys can lead to stress-shielding syndrome and late postoperative complications. The development of new Al- and V-free Ti alloys with a low elastic modulus is a critical task for implantology. Despite the relatively low Young modulus and appropriate biological response of metastable beta-Ti alloys, their production requires complex metallurgical solutions and a high final cost that limit commercial application. The current research aimed to develop a Zr-Ti-Nb system with a low Young modulus suitable for biomedical application, including orthopedics and dental implantology. Two different charges were used for new alloy production with melting in a vacuum-arc furnace VDP-1 under atmospheric control (argon + helium) with a non-consumable tungsten electrode and a water-cooled copper crystallizer. Post-treatment included a forging-rolling process to produce a bar suitable for implant production. SEM with EDX and the mechanical parameters of the new alloy were evaluated, and a cell culture experiment provided a biocompatibility assessment. The chemical composition of the new alloy can be represented as 59.57-19.02-21.41 mass% of Zr-Ti-Nb. The mechanical properties are characterized by an extremely low Young modulus—27,27 GPa for the alloy and 34.85 GPa for the bar. The different master alloys used for Zr-Ti-Nb production did not affect the chemical compound and mechanical parameters so it was possible to use affordable raw materials to decrease the final price of the new product. The cell culture experiment demonstrated a full biocompatibility, indicating that this new alloy can be used for dental and orthopedics implant production.
Keywords: Zr-Ti-Nb alloy; Young modulus; mechanical properties; biocompatibility